Determinación de la presencia de Helmintos gastro intestinales en gatos en las parroquias urbano marginales de la ciudad de Babahoyo - Marin Baquerizo, Allisson Natasha (2023)
This research consisted of determining Gastrointestinal Helminths in cats in the city of Babahoyo in the province of Los Ríos, between August and September 2023, where 60 fecal samples were collected to carry out a coprological study using smear and simple flotation methods. , this confirmed the existence of parasites. Of the samples taken in the Clemente Baquerizo Parish, 3 classes of parasites were found, which represented 7% Dipylidium, 7% Trichuris, and Toxocara cati with 13%. and 73% of negative cases. Of the 15 samples taken in the Camilo Ponce Parish, 1 class of parasites was found, Toxocara cati, which represents 7% and 93% of negative cases. Of the 15 samples taken in the Barreiro Parish, 13 positive cases of Toxocara cati were found, which represented 87%, and 2 negative cases, which represented 13%. Of the 15 samples taken in the El Salto Parish, all of them were positive for Toxocara cati, which represented 100%. The graph shows that felines up to 1 year of age represent 27%, while 2-year-old felines represented 46% and those over 2 years of age represented 27% of parasitized animals according to age. According to the graph, it shows us that the presence of helminths in felines according to sex represents 55% of males and 45% of females. The presence of helminths in felines according to their breed shows that mestizos reach a percentage of 67% while criollos have a percentage of 33%, which means that mestizos are the most affected. The graph shows that, of the 60 felines sampled, 55% of them were positive for Helminths and 45% were negative. The graph shows that, of the 33 felines sampled, 94% of them were positive for Toxocara cati, 3% for Dypilidium and 3% for Trichuris. Helminths and 45% Helminths present in the coproparasitic tests of the total sampled.